...or has it really turned? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A keen reader of Spore, Assaye Terefe, from East Gojjam, Ethiopia, is very worried, like others, about the effects of climate change on agriculture in his country. 'At the moment, cultivation methods based on former notions cause large-scale damage....